Regulation of reserve carbohydrates metabolism in Neurospora crassa: responses to pH, calcium and carbon source stresses and to the biological clock - Virgilio, Stela [UNESP] (2016)
The fungus Neurospora crassa, a model organism in studies of gene expression, metabolism, photobiology and circadian rhythm, is able to respond and adapt to different environmental stresses, such as heat shock, pH changes, nutrient limitation, osmotic stress, and others. Besides that, N. crassa has the genome sequenced and collections of knocked-out strains are avalaible to the scientific community. A systematic screening analysis performed with mutant strains in genes encoding transcription factors led to identify proteins involved in the glycogen metabolism regulation in this fungus. Glycogen and trehalose are storage carbohydrates that functions as a carbon and energy reserve. Trehalose can also protect membranes and proteins, increasing the tolerance to adverse conditions. In this work, some transcription factors were functionally characterized regarding their role in glycogen and trehalose metabolism regulation. The first condition investigated was the influence of the circadian clock in the glycogen metabolism. We observed that the glycogen accumulation and the expression of genes encoding glycogen synthase (gsn) and glycogen phosphorylase (gpn) are rhythmic in a wild-type strain and dependent on the FREQUENCY (FRQ) oscillator, the core component of the N. crassa circadian clock. The VOS-1 transcription factor, that is controlled by clock and can act in the connection between clock and glycogen metabolism, binds to gsn and gpn promoters rhythmically. However, the expression of gsn and gpn and the glycogen accumulation are still rhythmic in vos-1 strain, suggesting that not only VOS-1 but additional transcription factors could contribute to glycogen accumulation rhythmicity. Under pH and calcium stress, the PAC-3 transcription factor was investigated. First, we characterized the protein components of the pH signaling pathway, using the pal and pac-3 mutant strains. The mutants present high melanin production and inability to grow under alkaline pH. PAC-3 undergoes only one proteolytic cleavage, binds to pal promoters and regulates the expression of some pal genes under alkaline pH. PAC-3 is predominantly nuclear under alkaline condition and is able to bind to importin-α in vitro. Moreover, the components of pH signaling showed high glycogen and trehalose accumulation under normal and alkaline pH when compared to the wild-type. PAC-3 binds to some glycogenic and trehalose genes, and regulates their expression. Under calcium stress, pac-3 was induced and the carbohydrates metabolism was differently regulated. Finally, the CRE-1 transcription factor and the RCO-1 and RCM-1 cofactors, orthologs of the Mig1-Tup1-Ssn6 yeast complex, respectively, were investigated regarding their regulation of the glycogen metabolism under different carbon sources. CRE-1 is involved in catabolic repression and plays a role as repressor in glycogen regulation. CRE-1 binds in vivo and in vitro to gsn and gpn promoters, regulating their expression. This transcription factor is present in nucleus and cytoplasm in derepressed and starved conditions. RCO-1 and RCM-1 also regulated the glycogen accumulation, the glycogen synthase activity and the expression of some glycogenic genes, but do not play a major role in glycogen metabolism, while CRE-1 is the central regulator.